Decentralized Telescope Management for Satellite Tracking - Hafizoglu, Feyza Merve; Mailler, Roger (2013 IEEE/WIC/ACM International Joint Conferences on Web Intelligence (WI) and Intelligent Agent Technologies (IAT), 2013)
Currently, over 100 million objects orbit our planet in Low-Earth Orbit (LEO). To track these objects, the United States utilizes the Space Surveillance Network (SSN). However, numerous countries and corporations continue to expand their utilization of space leaving in their wake a sea of space debris. The rate that the number of objects is increasing has now outpaced our ability to build additional sites and there is an increasing concern for the safety of our astronauts and other space-borne assets. Another solution is to use large numbers of low-cost optical sensors, which can be easily deployed at a fraction of the cost of a traditional tracking station. However, the introduction of these systems, which are subject to time and position constraints, creates a complex coordination problem that must be solved in a communication limited environment. In this paper, we describe the satellite tracking problem and compare a resource allocation and scheduling representation for the problem. As an initial solution, scheduling tasks to telescope-slot pairs by a central facility is adopted. Then, we compare central and distributed repair mechanisms in terms of tasks completed and the communication cost. Finally, different distributed repair mechanism are proposed and compared.